The Expressionistic Features in the Drawings of Artist Abdul Razzaq Yasser: محمد فهمي عباس (Al-Academy, 2019)
To understand what the arts in general, and plastic arts in particular, have to do, it is necessary to know how they perform, not only that, but also to know their history, which we should understand at least in general terms. Which in turn gives an image of the standards of taste prevailing in each age, and some of the social and historical relationship of each era, and the cultural expression of that era, which is shown in the arts. We need to understand that the arts of each stage, although different from each other, yet remain interrelated in what we see through the effects that appear through the succession of times, which creates certain artistic traditions, inherited by one generation after the other. The research in this field deals with historical and artistic dimensions, which are determined by studying the works of expressionism as an artistic school and have appeared in the works of international artists and in Iraq in the works of Abdul Razzaq Yasser. The study included four chapters that covered the specific objectives of this study. The first stated the general framework of the research, which included the problem of research in determining expressionism as an artistic school that first appeared in Europe and how its features appeared in the work of artists? This chapter also included the importance of research and the need for it, according to a problem of direct items on the nature of the subject, and the objectives of the research were also presented. The second chapter included two sections: The first topic is expression and expressionism as an explanation of the term expression and what is expressionism as an artistic school and its history. It addresses expressionistic styles the in contemporary drawing and knowing the artists who worked in the context of this method since the emergence of the expressionistic school in Germany.The third chapter included the research procedures, which consisted of how to collect the research community, selecting the samples under study and analyzing the samples. The study ended with a presentation of the main findings of Chapter 4, and showing the most important conclusions, recommendations and proposals.